The space of fiction: language, aesthetics, politics - Pellejero, Eduardo (Geografares, 2016)
The rupture between the thought of nature as physis and human thought leadsto suffering and confusion for man in the fields of subjectivity. An affirmative relationshipwith becoming, in accordance with the proposal of Nietzsche's concept of dionysian wisdom, might lead man once again to the path of tragic life - one that produces strength byasserting pain and difference – thus surpassing the false opposition man/nature. Inspiredby Nietzsche, Deleuze and Guattari propose fighting against the fascism of the socius,the State, of capitalism and all the dominant discourses of established knowledge andestablished power that capture body and its will. An instrument for such struggle is theproduction of counterfascist erasures on the encodings of power. The question of howto produce bodies without organs as a way to escape the organic structure of the sociusis made possible by the power of sensation to erase and rediagram the cartographies ofsubjectivity
Keywords: erasure; cartography; socius